Microbial transformations of (−)-α- and (+)-β-thujone by fungi of Absidia species. (September 2015) - Gniłka, Radosław; Majchrzak, Wojciech; Wawrzeńczyk, Czesław
Graphical abstract: Highlights: Microbial transformations of α- and β-thujone (1a and1b ) afforded three new metabolites. The structures of new compounds were determined by 1D- and 2D-NMR analysis. The absolute configuration of all chiral centers in two new diols (5 and6 ) was elucidated. Abstract: The microbial transformations of (−)-α- and (+)-β-thujone (1a and1b ) in cultures of Absidia species: Absidia coerulea AM93, Absidia glauca AM254 and Absidia cylindrospora AM336 were studied. The biotransformations of (−)-α-thujone (1a ), by these fungi strains, afforded mixtures of 4-hydroxy- and 7-hydroxy-α-thujone (2 and3 ). Aforementioned fungi strains were also able to hydroxylate of (+)-β-thujone at C-7 position. Only A. glauca AM254 transformed1b to 8-hydroxy-β-thujone (7 ) and (2S)-2-hydroxyneoisothujol (6 ). The (4R)-4-hydroxyisothujole (5 ) was identified as one of the major metabolite of (+)-β-thujone (1b ) in culture of A. cylindrospora AM336. This strain was also able to introduce hydroxy group to C-4 position in1b without reduction of carbonyl group at C-3. The absolute configuration of all chiral centers of new (4R)-4-hydroxyisothujol (5 ) and (2S)-2-hydroxyneoisothujol (6 ) were established taking into account the configuration of (+)-β-thujone (1b ) and their spectral data.